2019
DOI: 10.1002/term.2981
|View full text |Cite
|
Sign up to set email alerts
|

Autologous blood coagulum is a physiological carrier for BMP6 to induce new bone formation and promote posterolateral lumbar spine fusion in rabbits

Abstract: In the present study, we describe autologous blood coagulum (ABC) as a physiological carrier for BMP6 to induce new bone formation. Recombinant human BMP6 (rhBMP6), dispersed within ABC and formed as an autologous bone graft substitute (ABGS), was evaluated either with or without allograft bone particles (ALLO) in rat subcutaneous implants and in a posterolateral lumbar fusion (PLF) model in rabbits. ABGS induced endochondral bone differentiation in rat subcutaneous implants. Coating ALLO by ABC significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 53 publications
1
51
0
Order By: Relevance
“…The efficacy and safety of this ABGS device for the treatment of critical size bone defects has been previously demonstrated in rabbits ( Grgurevic et al, 2019 ). To improve the implant biomechanical properties, we supplemented ABGS with allograft as a compression resistant matrix ( Vukicevic et al, 2020a ). Next, we tested synthetic ceramics of various chemical compositions (TCP, HA, BCP) formulated either as particles ( Stokovic et al, 2020a ) or blocks ( Stokovic et al, 2020b ) and demonstrated superior osteoconductive properties to support bone formation by rhBMP6 in ABC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The efficacy and safety of this ABGS device for the treatment of critical size bone defects has been previously demonstrated in rabbits ( Grgurevic et al, 2019 ). To improve the implant biomechanical properties, we supplemented ABGS with allograft as a compression resistant matrix ( Vukicevic et al, 2020a ). Next, we tested synthetic ceramics of various chemical compositions (TCP, HA, BCP) formulated either as particles ( Stokovic et al, 2020a ) or blocks ( Stokovic et al, 2020b ) and demonstrated superior osteoconductive properties to support bone formation by rhBMP6 in ABC.…”
Section: Discussionmentioning
confidence: 99%
“…Bone morphogenetic proteins (BMPs) are potent osteoinductive agents that recruit mesenchymal stem cells and promote their proliferation and differentiation into bone and cartilage during embryonic development ( Sampath and Vukicevic, 2020 ; Vukicevic and Grgurevic, 2009 ). Autologous blood coagulum (ABC) is a novel physiological BMP carrier that supports tight BMP binding to plasma proteins within the fibrin meshwork, suppresses foreign body response, and allows a sustained in vitro release of rhBMP6 ( Vukicevic et al, 2014 ; Grgurevic et al, 2019 ; Vukicevic et al, 2020a ; Vukicevic et al, 2020b ). To improve biomechanical properties of implants, compression resistant matrix (CRM) could be added to implants in selected indications ( Vukicevic et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…(9) ABGS induced new bone formation at 20 to 100 μg rhBMP6/mL coagulum in rat subcutaneous implants and restored the diaphyseal segmental defects in preclinical models. (9,10) ABC serves as a non-immunogenic physiological carrier. Furthermore, BMP6 has higher specific osteogenic activity than BMP2 and BMP7 presumably because it does not bind irreversibly to Noggin, a BMP antagonist, abundant in bone, compared with BMP2 and BMP7.…”
Section: Introductionmentioning
confidence: 99%